1, 3‐Dipolar Cycloaddition in the Synthesis of Novel Isoxazoline/Pyrazole Derivatives Bearing 1, 2, 3‐Triazoles Moiety. (18th May 2013) - Zeng, Yongming; Liu, Fangming
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>